Scenario Planning Development For Gold Retail Company - Khairunnisa, Nadia; Sunitiyoso, Yos (GEMA EKONOMI, 2023)
As time goes by, investment has become essential for the people of Indonesia. Gold is among the most popular instruments of the various investment instruments. Approximately 46% of Indonesians choose gold as the best investment method. This percentage is the highest compared to other investments, such as mutual funds (32%) and bank deposits (30%). PT EAY, a subsidiary of PT ANTAM Tbk, aims to enter and become a leading player in the retail business of gold, jewelry and domestic microbes. Scenario planning is needed to be able to find out the various uncertainties in the business environment. This study aims to identify the uncertainty factors affecting the gold retail industry and PT EAY over the next five years. This research is qualitative, with seven predetermined profile respondents from each category of stakeholders. The data used is primary data that has been collected through interviews and analyzed. The results of the interviews and analysis show that the most significant factor in the gold retail industry is influenced by two critical uncertainties: economic growth and technology. This study provides conclusions regarding scenarios to overcome future uncertainties and how to implement them. In order to be successful in the gold retail industry, companies must be able to create products that have advantages compared to other competitors and have an effective marketing strategy to expand the target market